Measurement of Some Hematological and Immunological Parameters in the Sera of Asthmatic Patients - Al-Naim, Samira (Iraqi Journal of Science, 2025)
The present study was carried out on (80) adults asthmatic patients (43 male and 37 female), their age from (25 -65) years. Some of them acute episodes while other between episodes interval.They were selected from out patients clinics of AL-Zahra’a hospital for allergy and asthma in Baghdad.All patients were diagnosed according to standard medical criteria as being asthmatic. The results of investigations were compared with those for a total of (20) healthy individual [(12) male & (8) female] with age (25 – 45) years, as a control group, throughout the period extended from ( July 2014 till December 2014).The patient samples were applied to determine complete blood count include (Hb, PCV, RBC count, WBC & Eosinophil count) in addition to (IL-8, GM-CSF) which estimated by ELISA technique.The results revealed that the mean Hb level for asthmatic patients were lower than normal value (9.3+ 1.4 g/L, 8.7+ 1.5 g/L) male & female respectively. More ever PCV, RBC, count values for both were nearly equal with in low values (26+ 4, 3.6 + 0.3 male, 25+ 3, 3.7+ 0.35 female).In this study the patients suffered from Iron deficiency anemia and nutritional deficiency. While leukocyte and eosinophile count values where higher than normal male: (12.5+ 0.5, 0.5 + 0.17), female: (12.6 + 0.6, 0.67 + 0.32) respectively and this due to asthmatic state.Most of sera patients had high concentration of Cytokine (IL-8& GM-CSF).The values concentration were found to be as high as (177pg/ml , 43 pg/ml) respectively in compared with healthy control (70 pg/ml , 8.2 pg/ml).